Analytics and Sports, part III: Improving resource allocation with portfolio decision analysis: Obstacles remain for widespread managerial adoption of analytics in professional sports, but the future looks promising. - Alamar, B.; Mehrotra, V. (Analytics, 2012)
Sports analytics will continue to evolve as a field. The pace of this evolution and adoption, however, will depend largely on how quickly leaders in sports become convinced that significant investments into analytics (data, models, information systems, and skilled personnel) will deliver a true competitive advantage. For the benefits of the explosion in data described in Part I of this series or advances in technology and analysis described in Part II to be captured by a team, the decision-makers will have to believe there is value in investing in these technologies and processes. This will not happen until analysts (and analytics champions, either inside or outside the organization) can effectively communicate that potential value to those executives. Today, while some teams are wading into the field, many still do not utilize sports analytics in any significant way, in part because they do not know where to start or how to integrate analytics into their organization. This is where the institutional structures described here in Part III can have a significant impact on the field. These training programs and research centers can provide well trained and experienced analysts, a trusted place for teams to find these analysts, and a source of advice on how to build an analytics program. The end result, we believe, will be a better set of data-driven tools and processes for more efficiently managing and making decisions in the world of professional sports, multibillion dollar industries that feature multimillion dollar payrolls, a variety of highly visible and complex decisions, and a growing set of opportunities for analytics.